Real-World Outcome of Platinum-Based Chemotherapy in Advanced Breast Cancer (ABC): A Retrospective Study from a Tertiary Cancer Center in India - Indhuja Muthiah Vaikundaraja; Manikandan Dhanushkodi; Venkatraman Radhakrishnan; Jayachandran Perumal Kalaiarasi; Nikita Mehra; Gangothri Selvarajan; Arun Kumar Rajan; Siva Sree Kesana; Balasubramanian Ananthi; Priya Iyer; Manjula Rao; Arvind Krishnamurthy; et al. (Indian Journal of Medical and Paediatric Oncology)
Introduction There is a paucity of data on platinum-based chemotherapy in advanced breast cancer (ABC) from developing countries like India.